PENINGKATAN PRODUK BERBASIS INOVASI UNIVERSITAS ANDALAS: SUATU STRATEGI INKUBASI BISNIS - Donard Games; Amri Syahardi (Jurnal Hilirisasi IPTEKS, 2020)
Universitas Andalas currently has produced many products which are based on highly quality research. These are, for example, gambir tea, mangosteen tea, and virgin coconut oil, which have been displayed in many exhibitions. The objective of this paper is to explain the importance of production of these innovative products which represents the continuation of business innovation in Universitas Andalas. However, it seems that most of them were produced solely because of some events or exhibitions rather than market demand. Because of that, we have had an initiative to increase the products quantity as a way of incubation strategy in Universitas Andalas. This means that, incubation can be seen as a way to enhance both business and product innovation. In addition to that, it should consider market related aspects such market demand and expectation.